Feasibility of transoral robotic selective neck dissection with or without a postauricular incision for papillary thyroid carcinoma: A pilot study - Tae, Kyung; Choi, Hae Won; Ji, Yong Bae; Song, Chang Myeon; Park, Jung Hwan; Kim, Dong Sun (Frontiers in Surgery, 2022)
Background: The study aimed to evaluate the feasibility of transoral robotic selective neck dissection (SND) with or without a postauricular incision for papillary thyroid carcinoma (PTC). Methods: We studied 14 patients with PTC who underwent robotic SND via the transoral or combined transoral and postauricular approaches. Results: The transoral approach was performed on 10 patients for dissection of levels III and IV. An additional postauricular incision was made on 4 patients for dissection of level II in addition to levels III, IV, and V. The operation was completed successfully in 13 patients, except 1 patient with the procedure conversion due to uncontrolled bleeding from the internal jugular vein. The mean numbers of removed lymph nodes in the lateral compartment were 23.1 ± 9.4 and 38.3 ± 8.5 in the transoral and combined groups. Transient recurrent laryngeal nerve palsy occurred in 1 patient, transient hypoparathyroidism in 3 patients, and chyle leakage in 1 patient. There were no hematomas, mental nerve injuries, surgical space infections, or CO2 embolisms. Conclusion: Transoral robotic SND is feasible with or without a postauricular incision.